Investigation of chitin grafting: thermal, antioxidant and antitumor properties - Cankaya, Nevin; Temuz, Mehmet Mursit; Can, Burak (Springer, 2025)
In this study, firstly chitin was reacted with chloracetyl chloride to synthesize the macroinitiator chitinchloroacetate (Ch.ClAc). Then, graft copolymers of methacrylamide (MAM), diacetone acrylamide (DAAM), N-(4-nitrophenyl)acrylamide (NPA), and 2-hydroxyethyl methacrylate (HEMA) monomers were synthesized by atom transfer radical polymerization (ATRP). All of the polymers were characterized by FTIR spectra and elemental analysis. According to the elemental analysis results, the mole percent (y) of the macro initiator was found to be 17.39%. The thermal stability of all the polymers (chitin, Ch.ClAc and its graft copolymers) was determined by thermogravimetric analysis (TGA) method and the highest thermal stability was observed in the ungrafted raw chitin. DPPH center dot scavenging activity and antitumor activity of all polymers were then investigated. Ch.ClAc was found to be the polymer that inhibited the proliferation of tumor cells more than chitin and graft copolymers. It was observed that the antitumor (L1210 cell lines) effect increased with increasing time and concentration in all polymers.
Keywords: Chitin; Graft copolymer; Thermal stability; Antioxidant; Antitumor